Platelet Pharmacytes for the Hierarchical Amplification of Antitumor Immunity in Response to Self‐Generated Immune Signals. Issue 23 (6th May 2022) - Yan, Jing; Liu, Xun; Wu, Fan; Ge, Chenglong; Ye, Huan; Chen, Xingye; Wei, Yuansong; Zhou, Renxiang; Duan, Shanzhou; Zhu, Rongying; Zheng, Yiran; Yin, Lichen
Abstract: Systemic immunosuppression mediated by tumor‐derived exosomes is an important cause for the resistance of immune checkpoint blockade (ICB) therapy. Herein, self‐adaptive platelet (PLT) pharmacytes are engineered to mediate cascaded delivery of exosome‐inhibiting siRNA and anti‐PD‐L1 (aPDL1) toward synergized antitumor immunity. In the pharmacytes, polycationic nanocomplexes (NCs) assembled from Rab27 siRNA (siRab) and a membrane‐penetrating polypeptide are encapsulated inside the open canalicular system of PLTs, and cytotoxic T lymphocytes (CTLs)‐responsive aPDL1 nanogels (NGs) are covalently backpacked on the PLT surface. Upon systemic administration, the pharmacytes enable prolonged blood circulation and active accumulation to tumors, wherein PLTs are activated to liberate siRab NCs, which efficiently transfect tumor cells, silence Rab27a, and inhibit exosome secretion. The immunosuppression is thus relieved, leading to the activation, proliferation, and tumoral infiltration of cytotoxic T cells, which trigger latent aPDL1 release. As such, the competitive aPDL1 exhaustion by PD‐L1‐expressing exosomes is minimized to sensitize ICB. Synergistically, siRab and aPDL1 induce strong antitumor immunological response and memory against syngeneic murine melanoma. This study reports a bioinspired mechanism to resolve the blood circulation/cell internalization contradiction of polycationic siRNA delivery systems, and renders an enlightened approach for the spatiotemporal enhancement of antitumor immunity. Abstract : Self‐adaptive platelet pharmacytes, consisting of encapsulated Rab27a siRNA nanocomplexes and backpacked anti‐PD‐L1 nanogels, are engineered to hierarchically amplify antitumor immunity. The platelet pharmacytes efficiently silence Rab27a in tumor cells to inhibit secretion of tumor‐derived exosomes, which relieves the immunosuppression and cascadingly releases anti‐PD‐L1 to sensitize anti‐PD‐L1‐mediated immune checkpoint blockade.